2017
DOI: 10.1111/ajgw.12313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of branched-chain amino acids to non-limited nitrogen synthetic grape must on volatile compounds and global gene expression during alcoholic fermentation

Abstract: Background and Aims The concentration and composition of nitrogen (N) in must is critical to yeast fermentation and aroma profiles in wine. We investigated the effect of adding branched‐chain amino acids (BCAAs, including l‐valine, l‐leucine and l‐isoleucine) to a non‐limited N medium on the formation of aromatic compounds and on gene expression patterns of the wine yeast Saccharomyces cerevisiae. Methods and Results A synthetic N‐sufficient must was supplemented with BCAAs and fermented with S. cerevisiae. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Different genes were identified and associated to yeast growth and amino acids transport; also 25 metabolites (higher alcohols, esters, fatty acids and branched-chain amino acid) were detected, among which 2,3-butanediol and ethyl lactate levels were highly increased. Therefore, it was suggested that the addition of branched chain amino acids was able to enhance aroma complexity [ 133 ]. All these techniques and studies have been developed to characterise different strains of S. cerevisiae that are tightly connected to differences in aroma compounds production, such in the case of a Gewürztraminer wine where a specific strain was able to produce increased amounts of 2-phenylethanol and cis-rose oxide and the most complex aroma profile [ 134 ].…”
Section: Strain Dependent Variability and Genetics Influence On Armentioning
confidence: 99%
“…Different genes were identified and associated to yeast growth and amino acids transport; also 25 metabolites (higher alcohols, esters, fatty acids and branched-chain amino acid) were detected, among which 2,3-butanediol and ethyl lactate levels were highly increased. Therefore, it was suggested that the addition of branched chain amino acids was able to enhance aroma complexity [ 133 ]. All these techniques and studies have been developed to characterise different strains of S. cerevisiae that are tightly connected to differences in aroma compounds production, such in the case of a Gewürztraminer wine where a specific strain was able to produce increased amounts of 2-phenylethanol and cis-rose oxide and the most complex aroma profile [ 134 ].…”
Section: Strain Dependent Variability and Genetics Influence On Armentioning
confidence: 99%
“…2-Phenylethanol (β-phenylethanol, 2-PE) is an aromatic alcohol with economic and research value that has comprehensive applications in edible essence or wine due to its favorable rose-like fragrance and stable properties [ 1 , 2 ]. Comprehensive applications cause considerable market demand to increase by 10%-15% every year, but 2-PE output is still in short supply.…”
Section: Introductionmentioning
confidence: 99%
“…Wilcox et al (2002) suggested that the function of PAU protein involves sterol transport, which might explain the substantial induction of PAU expression in HUF. Increased biomass can consume more nutrients (such as sterol, ions, copper, and thiamine) and cause nutrition deficiency, which can induce the expression of related functional genes to replenish these compounds (Liu et al, 2018). This could account for the increased expression of several genes ( PHO3 , ATX1 , and ATX2 ) by high UFA additions.…”
Section: Discussionmentioning
confidence: 99%
“…Thiamine pyrophosphate is a cofactor essential for the activity of pyruvate decarboxylase, and its depletion has a negative effect on yeast carbon metabolism (Hohmann and Meacock, 1998). Increasing the yeast biomass can consume a large amount of thiamine pyrophosphate, resulting in its deficiency in the must (Liu et al, 2018). The upregulation of ATX1 and ATX2 , which encode the Mn 2+ transporter, implies that the metal could also be limited in the cells (Lin and Culotta, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation